Effects of altered excitation–inhibition imbalance by repetitive transcranial magnetic stimulation for self-limited epilepsy with centrotemporal spikes - Yang, Yujiao; Han, Yixian; Wang, Jing; Zhou, Yongkang; Chen, Dong; Wang, Mengyang; Li, Tianfu (Frontiers in Neurology, 2023)
Objectives Patients with self-limited epilepsy with centrotemporal spikes (SeLECTS) with electrical status epilepticus in sleep (ESES) have generalized cognitive impairment, yet treatment options are limited. Our study aimed to examine the therapeutic effects of repetitive transcranial magnetic stimulation (rTMS) on SeLECTS with ESES. In addition, we applied electroencephalography (EEG) aperiodic components (offset and slope) to investigate the improvement of rTMS on the excitation–inhibition imbalance (E-I imbalance) in the brain of this group of children. Methods Eight SeLECTS patients with ESES were included in this study. Low-frequency rTMS (≤1 Hz) was applied for 10 weekdays in each patient. To assess the clinical efficacy and changes in E-I imbalance, EEG recordings were performed both before and after rTMS. Seizure-reduction rate and spike-wave index (SWI) were measured to investigate the clinical effects of rTMS. The aperiodic offset and slope were calculated to explore the effect of rTMS on E-I imbalance. Results Five of the eight patients (62.5%) were seizure-free within 3 months after stimulation, with treatment effects decreasing with longer follow-ups. The SWI decreased significantly at 3 and 6 months after rTMS compared with the baseline (P = 0.0157 and P = 0.0060, respectively). The offset and slope were compared before rTMS and within 3 months after stimulation. The results showed a significant reduction in the offset after stimulation (P < 0.0001). There was a remarkable increase in slope after the stimulation (P < 0.0001). Conclusion Patients achieved favorable outcomes in the first 3 months after rTMS. The ameliorative effect of rTMS on SWI may last up to 6 months. Low-frequency rTMS could reduce firing rates in neuronal populations throughout the brain, which was most pronounced at the site of stimulation. A significant reduction in the slope after rTMS treatment suggested an improvement in the E-I imbalance in the SeLECTS.